Про магнітне забруднення підкислення грунтів у приміській зоні Києва порівняно з фоновими аналогами - Бондар, К.М.; Макієнко, О.О.; Кузь, Ю.В. (Геоінформатика, 2015)
Исследована взаимосвязь между удельной магнитной восприимчивостью (χ) и водородным показателем (pHKCl) дерновых и дерново-подзолистых почв на двух опытных участках: в лесопарковой зоне Пуща-Водица (Киев) и около пгт Клавдиево-Тарасово (Киевская обл.). Величина c поверхностного горизонта почв на участке Пуща-Водица изменяется в пределах (5÷77)10⁻⁸ м³/кг, в Клавдиево-Тарасово — (5÷26)10⁻⁸ м³/кг. Зоны высоких значений χ на участке Пуща-Водица тяготеют к автодорогам с интенсивным транспортным движением. По результатам анализов высокотемпературного поведения магнитной восприимчивости в составе почв участка Пуща-Водица установлен техногенный магнетит. Показано, что образцы почв с высокими значениями c характеризуются низкими значениями pHKCl , т. е. выявлена обратная корреляционная зависимость между этими параметрами (r = —0,57). Для образцов почв фонового участка Клавдиево-Тарасово такой тенденции не отмечено. Полученные данные свидетельствуют об общем пути кислотного и магнитного загрязнения почв окрестностей Киевской городской агломерации — выпадении твердых и жидких осадков из атмосферы. Досліджено зв’язок між питомою магнітною сприйнятливістю (χ) та водневим показником pHKCl дернових і дерново-підзолистих ґрунтів на двох дослідних ділянках: лісопаркової зони Пуща-Водиця (Київ) та біля смт Клавдієво-Тарасове (Київська обл.). Величина c поверхневого горизонту ґрунтів першої ділянки змінюється в межах (5÷7)10⁻⁸ м³/кг, другої — в межах (5÷26)10⁻⁸ м³/кг. Зони високих значень c на ділянці Пуща-Водиця тяжіють до автошляхів з інтенсивним транспортним рухом. За результатами аналізів високотемпературної поведінки магнітної сприйнятливості ґрунти ділянки Пуща-Водиця містять техногенний магнетит. Показано, що зразки ґрунту з високими значеннями χ ділянки характеризуються низькими значеннями pHKCl, тобто спостерігається обернена кореляційна залежність між цими параметрами (r = —0,57). Для зразків ґрунту з фонової ділянки Клавдієво-Тарасове такої тенденції не встановлено. Отримані дані свідчать про спільний шлях кислотного та магнітного забруднення ґрунтів околиць Київської міської агломерації, яким є випадіння твердих і рідких опадів з атмосфери. Purpose. The purpose of the article is to prove a hypothetic possibility of their existing a conjoint way of magnetic and acid soil contamination of the Kyiv city metropolitan area outskirts. Design/methodology/approach. The dependence between magnetic susceptibility (χ) and hydrogen parameter pHKCl in soddy and soddy-podzolic soils is studied in two research areas: the park area Pushcha-Voditsa (Kyiv city, Ukraine) and the area near the village Klavdiyevo-Tarasove located 40 km far from the city. Findings. χ of surface soil horizon in Pushcha-Voditsa varies from 5 to 77·10⁻⁸ m³/kg, in Klavdiyevo-Tarasove – within 5...26·10⁻⁸ m³/kg. Areas with high values of χ in Pushcha-Voditsa tend to be closer to roads with heavy traffic. The traces of magnetic pollution defined based on the analysis of the high-temperature behavior curves of the magnetic susceptibility of soils from Pushcha-Voditsa. In the soil from Pushcha-Voditsa, as well as in the contaminated samples from the streets of Kyiv city with relatively high isothermal χ , a wide and high peak in the vicinity of 5000 was observed, interpreted as Hopkin peak, which is characteristic of fine single-domain magnetite, likely of anthropogenic origin. It is shown that the samples from Pushcha-Voditsa with high χ are likely to have low pHKCl values, i.e., there is a negative correlation between these parameters (r = –0.57). No such trend observed for the samples from the background area of Klavdiyevo-Tarasove. Practical value/implications. The results obtained suggest a conjoint way of magnetic and acid soil contamination of the Kyiv city metropolitan area outskirts, which is a fallout of solid and liquid precipitation from the atmosphere. As a result of the high temperature transformation of iron sulfides contained in coal and other natural fuels of power plants, a particular substance comprising iron oxides and sulfur dioxide, which causes acidification of precipitation, is emitted to the atmosphere. Due to a high concentration of exhaust gases in the surface air in the vicinity of roads with heavy traffic, fine magnetic particles and nitric acid, which is formed as a result of the interaction of nitrogen dioxide with water, reach the soil.